2018
DOI: 10.1016/j.micpath.2018.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Role of secondary metabolites in plant defense against pathogens

Abstract: Pathogens get entry into host cell, reproduce there and use biological machinery of host plants which is threat to global crop production. Integrated management strategies based upon minimizing population and use of resistant cultivars can address this potential problem. In developing world farmers are less likely to adopt these approaches instead they prefer the use of chemical pesticides. Reckless use of chemical pesticides is destroying our ecosystem. That's why it is required to explore ecofriendly alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
248
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(301 citation statements)
references
References 80 publications
3
248
0
3
Order By: Relevance
“…Phenolics are among the secondary metabolites that are involved in plant protection [58]. In this study, the accumulation of phenolics content was noticed, accompanied with infection and/or H 2 O 2 treatments.…”
Section: Treatmentsmentioning
confidence: 60%
“…Phenolics are among the secondary metabolites that are involved in plant protection [58]. In this study, the accumulation of phenolics content was noticed, accompanied with infection and/or H 2 O 2 treatments.…”
Section: Treatmentsmentioning
confidence: 60%
“…First, plants have physical obstacles, such as waxes, dense cuticles, and special trichomes, which stop pathogens or insects from settling on plants. Furthermore, plants generate chemical complexes to protect themselves against herbivores and pathogens [4]. Additionally, plants can recognize pathogens via two pathways that activate defense responses.…”
Section: How Plants Defend Themselves Against Biotic Stressesmentioning
confidence: 99%
“…However, the production of these substances can be influenced by responses to herbivorous attacks and suffer interference from seasonal factors such as altitude, lighting, and seasonality, which directly affects their biological properties. [1,2] Studies have shown that essential oils have significant antifungal effects against Candida spp. [3] and dermatophytes, as Trichophyton rubrum, Trichophyton mentagrophytes, Microsporum canis, Microsporum gypseum, Epidermophyton floccosum, among others.…”
Section: Introductionmentioning
confidence: 99%